Iodine-catalyzed oxidative multiple C–H bond functionalization of isoquinolines with methylarenes: an efficient synthesis of isoquinoline-1, 3, 4(2H)-triones. Issue 34 (21st August 2017) - Zhu, Di; Luo, Wen-Kun; Yang, Luo; Ma, Da-You
Abstract : An iodine-catalyzed multiple C–H bond functionalization of isoquinolines with methylarenes via a successive benzylic sp 3 C–H iodination/ N -benzylation/amidation/double sp 2 C–H oxidation sequence to yield isoquinoline-1, 3, 4(2 H )-triones is developed for the first time. Abstract : An iodine-catalyzed multiple C–H bond functionalization of isoquinolines with methylarenes via a successive benzylic sp 3 C–H iodination/ N -benzylation/amidation/double sp 2 C–H oxidation sequence is developed. This reaction utilizes un-functionalized isoquinolines and readily available methylarenes as starting materials, proceeds under metal-free conditions, and avoids a multi-step experimental operation, to make it an efficient and practical method for the synthesis of N -benzyl isoquinoline-1, 3, 4-triones.